MANAJEMEN STRATEGI ISLAMI TERHADAP PENGELOLAAN PASAR TRADISIONAL ASEMBAGUS SITUBONDO DALAM MENGHADAPI PERSAINGAN PASAR MODERN - Zuhriyah Zuhriyah; A. Muhyiddin Khotib; Zainol Hasan (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
Strategic management is a series of processes to organize and manage strategies that will be carried out in a business with certain goals and long-term goals through the processes of planning, organizing, actuating and organizing. Meanwhile, Islamic strategic management is managing a business that is run by remaining in the pleasure of Allah and free from the prohibition of usury. The management strategy referred to here is seen as necessary to apply in public markets as well as to maintain the existence of traditional markets in the midst of the rise of modern markets. The strategy taken at the Asembagus public market is in addition to making voices, rearranging the stalls and stalls, and preparing trolleys and baskets at the market door to make it easier for buyers. In addition, an Islamic market management system is also applied, namely by holding prayers and reciting the Koran together regularly every month every Maghrib prayer and every Legi Thursday night. The results of this study prove that by using strategic management in an Islamic way, it will further launch a business and the business that is run will be free from usury so that the results obtained are more blessed and beneficial.